Tinjauan Yuridis terhadap Peran OJK dalam Penanggulangan Investasi Ilegal: Studi Putusan Nomor 1240/PID.SUS/2022/PN TNG - Chatrine Tryana Purba; Elvira Fitriyani Pakpahan Pakpahan (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The proliferation of digital-based illegal investment schemes in Indonesia has caused substantial financial harm to the public and raises questions about the extent of the Financial Services Authority's (OJK) role in its prevention. This study aims to analyze OJK's authority in combating illegal investment, OJK's role in providing legal protection to investors in Decision Number 1240/Pid.Sus/2022/PN Tng, and the effectiveness of illegal investment law enforcement along with OJK's limitations. A normative juridical method with a descriptive-analytical approach was employed, drawing on secondary data comprising legislation, court decisions, and legal literature. The findings indicate that OJK's authority under Law Number 21 of 2011 is normatively strong yet operationally constrained due to the absence of direct criminal law enforcement powers. In Decision Number 1240/Pid.Sus/2022/PN Tng, OJK actively supported law enforcement by submitting reports to the National Criminal Investigation Agency and providing expert testimony; however, it failed to deliver substantive protection to victims as all confiscated assets were forfeited to the state. Law enforcement effectiveness remains low owing to four structural obstacles: an authority gap between OJK and criminal law enforcement agencies, limited jurisdiction over foreign-based platforms, low public financial literacy at 49.68 percent, and inadequate victim protection mechanisms. Revision of the OJK Law, a paradigm shift toward restorative justice, strengthened digital financial literacy, and the enactment of comprehensive digital illegal investment regulations are recommended.